Role of nerve signal transduction and neuroimmune crosstalk in mediating the analgesic effects of acupuncture for neuropathic pain - Chen, Yong; Li, Dan; Li, Ningcen; Loh, PeiYong; Guo, Yi; Hu, Xiyou; Zhang, Jingyu; Dou, Baomin; Wang, Lifen; Yang, Chaobo; Guo, Tao; Chen, Shuangli; et al. (Frontiers in Neurology, 2023)
Neurogenic pain rises because of nervous system damage or dysfunction and is the most difficult to treat among other pathological pains. Acupuncture has been reported as a great treatment option for neurogenic pain owing to its unlimited advantages. However, previous studies on the analgesic effects of acupuncture for NP were scattered and did not form a whole. In this study, we first comprehensively review the relevant basic articles on acupuncture for NP published in the last five years and summarize the analgesic mechanisms of acupuncture in terms of nerve signaling, neuro-immune crosstalk, and metabolic and oxidative stress regulation. Acupuncture inhibits the upstream excitatory system and suppresses neuronal transmission efficiency by downregulating glutamate, NMDA receptors, P2XR, SP, CGRP and other neurotransmitters and receptors in the spinal cord, as well as plasma channels such as TRPV1, HCN. It can also activate the downstream pain inhibitory pathway by upregulating opioid peptide (β-endorphin), MOR receptors, GABA and GABA receptors, bi-directional regulating 5-hydroxytryptamine (5-HT) and its receptors (upregulate 5-HT 1A and downregulate 5-HT7R) and stimulating hypothalamic appetite-modifying neurons. Moreover, neuroinflammation in pain can be inhibited by acupuncture through inhibiting JAK2/STAT3, PI3K/mTOR pathways, down regulating chemokine receptor CX3CR1 on microglia and up regulating adenosine receptor A1Rs on astrocytes, inhibiting the activation of glia and reducing TNF-α and other inflammatory substances. Acupuncture also inhibits neuronal glucose metabolism by downregulating mPFC’s GLUT-3 and promotes metabolic alterations of the brain, thus exerting an analgesic effect. In conclusion, the regulation of nerve signal transduction and neuroimmune crosstalk at the peripheral and central levels mediates the analgesic effects of acupuncture for neuropathic pain in an integrated manner. These findings provide a reliable basis for better clinical application of acupuncture in the management of neuropathic pain.